γ-Aminobutyric acid (GABA) production and soluble free amino acid profile change in Andean seeds by Levilactobacillus brevis fermentation - Ibieta, Gabriela; Ortiz-Sempértegui, Jimena; Grey, Carl; Peñarrieta, J. Mauricio; Linares-Pastén, Javier A. (Frontiers in Nutrition, 2025)
High nutritional value Andean seeds—tarwi (Lupinus mutabilis), cañihua (Chenopodium pallidicaule), and quinoa (Chenopodium quinoa)—were subjected to solid-state fermentation with Levilactobacillus brevis DSM 1269. This strain can convert L-glutamic acid into the neurotransmitter GABA. Fermented tarwi exhibited the highest GABA production, at 4 mg/g sample, which correlates with its higher protein content compared to fermented quinoa and cañihua, at 1 mg/g and 0.3 mg/g, respectively. Seeds kept at room temperature before fermentation produced higher concentrations of GABA compared to seeds kept at 4 °C. Autoclaving, a mandatory step for fermentation, resulted in a decrease in L-glutamic acid in tarwi seeds and an increase in quinoa and cañihua seeds. Additionally, fermentation produced lactic acid and acetic acid, together with an increase in the content of free essential amino acids, including threonine, histidine, methionine, isoleucine, leucine, valine, and lysine. This work demonstrated, for the first time, the functional valorisation of tarwi, cañihua, and quinoa through the production of bioactive metabolites and the enhancement of essential free amino acids via fermentation with L. brevis.